Pengaruh Penerapan E-Filing pada Kepatuhan WPOP dengan Sosialisasi Perpajakan dan Pemahaman Internet sebagai Variabel Pemoderasi - Laksmi Puspita Yanti, Putu; Ery Setiawan, Putu (E-Jurnal Akuntansi, 2020)
This study aims to determine the effect of the application of e-filing on compliance of individual taxpayers in North Badung Primary Tax Office with tax dissemination and internet understanding as moderating variables. The number of samples used in this study were 100 respondents out of 26,624 populations of individual taxpayers in North Badung Primary Tax Office in 2019. The data analysis technique used are simple linear regression test and the Moderated Regression Analysis (MRA) interaction test. The results showed that the application of e-filing has a positive and significant effect on the compliance of individual taxpayers in North Badung Primary Tax Office. Tax socialization and internet understanding was not able to moderate the effect of implementing e-filing on the Obligatory Compliance of Individuals in North Badung Primary Tax Office. Keywords: E-Filing; Tax Dissemination; Internet Understanding; Personal Taxpayer Compliance.